Upaya Guru PAI dalam Internalisasi Nilai-Nilai Moderasi Beragama di SMK Negeri 1 Wonosobo - Lia Warih Perwitasari; Ahmad Khoiri; Vava Imam Agus Faisal (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
This study aims to determine the efforts of Islamic Religious Education (PAI) teachers in internalizing the values ​​of religious moderation at SMK Negeri 1 Wonosobo, the results achieved, and the supporting and inhibiting factors in its implementation. This study used a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that PAI teachers internalize the values ​​of religious moderation through classroom learning, role models, habits, school culture, and strengthening national values. The values ​​instilled include tolerance, justice, balance, anti-violence, and respect for diversity. The results of internalization are seen from students' good understanding of religious moderation, mutual respect, and tolerant behavior in school life. Supporting factors include teacher role models, school support, a conducive environment, and parental involvement, while inhibiting factors include the influence of social media, differences in students' religious backgrounds, and limited learning time. Based on the research results, it can be concluded that the internalization of religious moderation values ​​at SMK Negeri 1 Wonosobo is progressing well and contributing to the development of moderate, tolerant, and respectful students' character.